2000
DOI: 10.1007/s101570070027
|View full text |Cite
|
Sign up to set email alerts
|

The methylguanidine-to-creatinine ratio, serum NOx concentrations, and vascular disease in nondiabetic hemodialysis patients

Abstract: Background. Hemodialysis (HD) patients are in a highly oxidative state, which may contribute to accelerated atherosclerosis. Methylguanidine (MG) and lipid peroxides may be used as markers of the oxidative status in HD patients. A recent study demonstrated the non-enzymatic generation of nitric oxide (NO) via a reaction between hydrogen peroxide and arginine. We determined the relationships between serum concentrations of the oxidation products of NO (NOx) and oxidative status markers, and the relationships be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The increased level of MG in CSA patients as compared to NC is suggestive of increased oxidation of creatinine with hydroxyl radicals via creatol (15,18). Studies have also demonstrated a correlation between serum creatinine and MG levels, which supports the idea of the oxidative stress of disease (15,16).…”
Section: Significance Of Metabolic Signature Biomarkersmentioning
confidence: 61%
See 3 more Smart Citations
“…The increased level of MG in CSA patients as compared to NC is suggestive of increased oxidation of creatinine with hydroxyl radicals via creatol (15,18). Studies have also demonstrated a correlation between serum creatinine and MG levels, which supports the idea of the oxidative stress of disease (15,16).…”
Section: Significance Of Metabolic Signature Biomarkersmentioning
confidence: 61%
“…Two independent approaches measured one constituent and found that similar observations further validated the precision of the results. An augmented level of creatinine may help MG production causing neutrophils stimulation through free radicals, cytokines, and other peroxides (15)(16)(17) and supports the idea of oxidative stress of the disease, as explained above in detail.…”
Section: Significance Of Clinical Signature Variablesmentioning
confidence: 61%
See 2 more Smart Citations